Сучасні проблеми оплати праці в Україні в умовах кризи національної економіки - Базалійська, Н. П.; Кравець, С. А.; Bazaliyska, N.; Kravec, S. (КНТУ, 2015)
Стаття присвячена висвітленню проблем оплати праці в Україні за сучасних умов господарювання. Здійснено оцінку рівня добробуту населення на основі аналізу основних показників оплати праці, що включають рівні мінімальних соціальних стандартів, у тому числі номінальної і реальної мінімальних заробітних плат. Виявлено причини низької купівельної спроможності (реальної зарплати) українських громадян. Визначено особливості середньої та середньомісячної заробітних плат в умовах девальвації національної валюти. Проаналізовано динаміку змін сум заборгованості з виплати заробітної плати та обґрунтовано причини їх наявності. The dynamics of the Ukrainian economy in 2013 is largely determined by global and European economic trends. However, already the end of 2013 and beginning of 2014 was the beginning of a new era for Ukraine. The activation of crisis tendencies in the economy of Ukraine was observed recently, due to the consequences of Russian aggression and serious systemic economic deformities that accumulated from the 90s to the present. Wages is staying one of the main tools of social and economic policy regardless of the economic system (planned or market). The aim of the study is the formation of a holistic view of the current problems of pay in a systemic economic crisis. Special attention is paid to analysis of the main indicators that characterizing the level of welfare of Ukrainian, salary indices and consumer prices and wage arrears in a systemic crisis. It was determined that the indexation of wages is a state guarantee that is only partially protects the public from the increase in consumer prices for goods and services. The reasons for the low level of wages Ukrainians and late payment of wages have been identified. The study showed that the dynamics of the main indicators of wage does not provide a reliable basis for the growth of the welfare of the citizens of Ukraine etc.
Modern Problems of Wages in Ukraine in the Conditions of the Crisis of National Economy
Keywords: оплата праці; заробітна плата; індекс споживчих цін; індекс реальної заробітної плати; мінімальна заробітна плата; прожитковий мінімум; заборгованість з виплати заробітної плати; wages; the consumer price index; the index of real wages; minimum wage; living wage; arrears of wages